Detection of Magma Beneath the Northern and Southern Rift Zones of Axial Seamount at the Juan de Fuca Ridge - Michelle K. Lee; Suzanne M. Carbotte; Adrien F. Arnulf (Geochemistry, Geophysics, Geosystems)
Abstract Axial Seamount is an active hotspot‐related volcanic system located along the Juan de Fuca Ridge (JdFR) that includes a central volcano and bounding northern and southern rift zones (NRZ and SRZ). Three documented volcanic eruptions in 1998, 2011, and 2015 included dike propagation into and eruptions within the rift zones that are believed to have been sourced from the well‐imaged large magma reservoir found beneath the central volcano. However, areas beyond the central volcano have not been explored for potential magma sources that could have contributed to these events, and geochemical studies of older rift zone lavas indicate differences in compositions suggestive of magma reservoirs fed by more mid‐ocean ridge‐dominated mantle sources. In this study, we analyze multichannel seismic data acquired in 2002 to characterize the internal crustal structure of the rift zones. The new reflectivity images reveal small (<5 km wide) and discontinuous crustal magma bodies at depths of ∼1.5 to 4 km beneath and in the vicinity of the rift zone lava flows from the three eruptions. We also image wide magma bodies within the overlap regions between the rift zones and neighboring segments of JdFR including a 6.4 km wide body under the east flank of NRZ and a 1‐km wide, ∼400 to 500 m, thick body near the base of the crust under the SRZ‐Vance overlap basin. Collectively the new observations indicate that multiple small crustal magma bodies underlie Axial segment, in addition to the main reservoir, and likely contribute to rift zone magmatism with implications for interpretations of seismicity patterns and lava flow compositions.